Analysis Of User Satisfaction Level On Services At The Port Of Flosing Bungus City, Padang City, West Sumatra - Chairul Insani Ilham; Kodrat Alam; Arman Saputra (IWJ : Inland Waterways Journal, 2022)
Bungus Bay Ferry Port is located in West Sumatra Province. Bungus Bay Ferry Port is a ferry port that has a very important role for the community, especially in the Mentawai Islands Regency. Because the Bungus Bay Ferry Port can improve the economy of the Mentawai Islands Regency in the transportation sector. Based on the results of observations in the field, there are several services that have not been carried out properly, so that service users feel less satisfied and comfortable while at the Bungus Bay Ferry Port. The methods used to analyze the existing problems are the Customer Statisfaction Index, Gap analysis, and Importance Performance Analysis. Based on the results of the analysis, it was found that the passenger satisfaction index was 67.08% and there were 5 service attributes in quadrant I that had to be improved and improved in quality. Based on the results of the analysis, it can be concluded that there are several service attributes that are not running optimally, the service attributes include safety facilities such as fire extinguishers, evacuation route instructions, evacuation gathering points, first aid facilities, complaint telephone numbers, dividing lines between gangways and lanes. vehicles, ample parking space with good circulation in and out.